2023
DOI: 10.1039/d2qi02122f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-induced phase transformations of hybrid tin bromide single crystals enable the occurrence of second-harmonic generation

Abstract: Phase transformations of tin halide hybrid materials have played an important role in the formations of structural diversity and optoelectronic versatility due to the oxidability and instability from Sn2+ to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
(78 reference statements)
2
10
0
Order By: Relevance
“…A band gap value of approximately 2.60 eV is shown in the inset of Figure d, which is comparable to the value of the previously reported Sn­(IV) halide (2.64 eV). In line with the earlier study, the band gap of the Sn­(IV) material after DRST is smaller than that of the Sn­(II) material . As opposed to their enantiomers, S -2-mpip­[SnBr 3 ]Br and S -2-mpipSnBr 6 have band gaps of about 2.89 and 2.62 eV, respectively, while rac -2-mpip­[SnBr 3 ]Br has a band gap of around 2.55 eV.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A band gap value of approximately 2.60 eV is shown in the inset of Figure d, which is comparable to the value of the previously reported Sn­(IV) halide (2.64 eV). In line with the earlier study, the band gap of the Sn­(IV) material after DRST is smaller than that of the Sn­(II) material . As opposed to their enantiomers, S -2-mpip­[SnBr 3 ]Br and S -2-mpipSnBr 6 have band gaps of about 2.89 and 2.62 eV, respectively, while rac -2-mpip­[SnBr 3 ]Br has a band gap of around 2.55 eV.…”
Section: Resultssupporting
confidence: 89%
“…R / S -2-mpip­[SnBr 3 ]­Br were crystallized under atmospheric conditions using the cooling crystallization method to produce colorless rod-like single crystals. Based on previously reported redox potential, H 3 PO 2 was added in a 5:1 ratio, which caused the yellow solution to change into a colorless, clear solution to inhibit the oxidation of Sn 2+ and Br – in the HBr solution. The heating temperature was maintained at 70 °C for half an hour to ensure that the starting materials were completely dissolved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, most of the research focused on lead (Pb) metal halides. However, the most serious issue lies in the toxicity of Pb. It is urgent to develop environmental-friendly lead-free metal halides with low-toxicity elements, such as copper (Cu), tin (Sn), antimony (Sb), , and manganese (Mn). Among lead-free metal halides, Mn­(II)-based metal halides with a d 5 configuration that possesses the d–d transition exhibit outstanding optical characteristics. Currently, Mn­(II)-based hybrid halides have attracted much interest due to their unique luminescent color and directly observed luminescent conversion. As we all know, Mn 2+ ions with tetrahedral coordination, in which each Mn 2+ is coordinated with four halogen (X) anions to form an [MnX 4 ] 2– tetrahedral unit, exhibit green emission due to the weak ligand/crystal field strength around Mn 2+ ions. On the contrary, Mn 2+ ions with octahedral coordination, where each Mn is coordinated with six halogen anions to form an [MnX 6 ] 4– octahedral unit, exhibit red emission due to the strong ligand/crystal field strength surrounding Mn 2+ ions. , Interestingly, the coordination environment of Mn 2+ ions can be adjusted between the octahedron and tetrahedron by certain methods, such as temperature, humidity, and pressure, which leads to the variations of luminescent color of Mn­(II)-based hybrid halides. , A reversible conversion between the green emission of (C 5 H 8 N 2 ) 2 MnCl 4 (1-ethylimidazole) and red emission of C 5 H 8 N 2 (MnCl 2 ) x Cl y was demonstrated by Fu et al Zheng et al found an interesting luminescent conversion between green-emitting TMAMnCl 3 and red-emitting TMA 2 MnCl 4 (TMA = tetramethylammonium) that can be achieved by adding corresponding raw MnCl 2 or TMACl precursors .…”
Section: Introductionmentioning
confidence: 99%